Sistem Informasi Penyewaan Mobil Berbasis Web Pada PT. Frasindo Lima Mandiri - Shany Liany Saepudin; Rani Puspita Dhaniawaty (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2019)
Current developments and advances in technology and information in Indonesia have begun to develop and can be utilized to develop business. PT. Frasindo Lima Mandiri is a company engaged in car rental services. In the rental process, the customer must come to the company to find out the type and availability of cars rented by the company. The payment process is still recorded in the payment journal, so that company employees will have difficulty in checking the status of customer payments. Seeing the problems that occur in the rental process, the purpose of this research is to create a web-based car rental information system. With this rental car information systems can simplify data management and provide complete information related to car rental. The method used in this study is the prototype system development method, analysis and design tools used are UML (Unified Modeling Language). The results of this study are that customers can find information related to rental cars, make car rental transactions online, can facilitate employees in the process of finding customer payment data and companies can provide services more quickly and accurately.